Strategies of Islamic Education Teachers in Internalizing Religious Moderation Values Among Students at SMPN 1 Tangerang - Sutarman Sutarman; Agus Salim; J. Anhar Rabi Hamsah Tis’ah; Abdul Basyit; Achmad Fuazi; Nasrullah Nasrullah (Journal of Pedagogi, 2025)
This study aims to describe the religious moderation values among students at SMPN 1 Tangerang and to outline the strategies employed by Islamic Education teachers to internalize these values in students. The research uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, participatory observation, and documentation. Data analysis included data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured through triangulation. The findings of the study include: (1) Religious moderation values through four indicators: national commitment, tolerance, anti-violence, and accommodation of local culture, as reflected in flag ceremonies, Pancasila education, national defense, religious lessons according to each student's faith, and wearing traditional clothes; (2) The strategies of Islamic Education teachers in internalizing religious moderation values include: a) Stages of introduction, acceptance, and integration in lessons; b) Approaches of experience, habituation, emotional, rational, functional, and role modeling through various religious activities and learning materials that promote mutual respect; c) Strategies of traditional, flexible, reflective, and trans-internal methods applied by PAI teachers in the classroom, especially for non-Muslim students, participatory learning, and leading by example